Basic and advanced structural equation modeling with applications in the medical and behavioral sciences - Lee, Sik-Yum (Wiley series in probability and statistics., 2012)
"This book introduces the Bayesian approach to SEMs, including the selection of prior distributions and data augmentation, and offers an overview of the subject's recent advances"--